2007
DOI: 10.1152/jn.01272.2006
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Reflexes and Synergies Triggered by an Unexpected Support Surface Height During Walking

Abstract: van der Linden MH, Marigold DS, Gabreëls FJM, Duysens J. Muscle reflexes and synergies triggered by an unexpected support surface height during walking. J Neurophysiol 97: 3639 -3650, 2007. First published March 28, 2007 doi:10.1152/jn.01272.2006. An important phase in the step cycle is foot contact. When the moment of foot contact differs from the one expected, a fast response is needed. Such a mismatch can be caused by hitting a support surface earlier or later than expected. To study this, experiments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 41 publications
11
76
1
Order By: Relevance
“…Such a visually guided pre-adaptation is not possible in experiments where the changes in ground level are invisible because of camouflage and occur by chance. Experiments on humans walking along a walkway with an unexpected loss of ground support have shown that in the unexpected lowered contact the absence of expected heel contact triggered responses in the ipsilateral antigravity muscles and contralateral flexor muscles (Shinya et al, 2009;van der Linden et al, 2007), and that after touchdown humans reset the gait rhythm to permit continued walking by delaying the subsequent take-off (Shinya et al, 2009;van Dieën et al, 2007). Compared with walking, during running the duration of the stance phase is shorter and thus adjustments may be necessary prior to contact.…”
Section: Introductionmentioning
confidence: 99%
“…Such a visually guided pre-adaptation is not possible in experiments where the changes in ground level are invisible because of camouflage and occur by chance. Experiments on humans walking along a walkway with an unexpected loss of ground support have shown that in the unexpected lowered contact the absence of expected heel contact triggered responses in the ipsilateral antigravity muscles and contralateral flexor muscles (Shinya et al, 2009;van der Linden et al, 2007), and that after touchdown humans reset the gait rhythm to permit continued walking by delaying the subsequent take-off (Shinya et al, 2009;van Dieën et al, 2007). Compared with walking, during running the duration of the stance phase is shorter and thus adjustments may be necessary prior to contact.…”
Section: Introductionmentioning
confidence: 99%
“…to smoothly absorb energy by eccentric contraction of the ankle plantar-or dorsiflexors, such as normally observed in heel and toe landings, is impaired in this position [14,16,17]. In a previous study, reduced activity of the dorsiflexors prior to foot contact was indeed found in the unexpected level walking condition [20].…”
Section: Discussionmentioning
confidence: 78%
“…expected [20]. It was found that the muscle activity preceding foot contact indeed differed from trials with an expected moment of landing.…”
Section: Introductionmentioning
confidence: 82%
“…"These findings indicate that, in addition to generating fast corrective response, the lumbar spinal cord generated some adjustments in hindlimb stepping patterns through experience" (Heng and de Leon, 2007, p. 8561). Such processes are also under descending cerebellar (van der Linden et al, 2007) and cerebral cortical (Kimura et al, 2006) control, and can even be modified voluntarily in humans after biofeedback training (Ludvig et al, 2007).…”
Section: Spinal Adjustment Reflexesmentioning
confidence: 99%
“…Controversy exists as to whether the models so acquired are stored in the cerebellum , or cerebral cortex areas such as the parietal area . The actual submovements so scheduled for task mastered motor skills might be directly controlled from the cerebral cortex (Heffner and Masterton, 1983;Kuyper, 1958;Liscic et al, 1998;Ludlow, 2005;Maertens de Noordhout et al, 1999;Teitti et al, 2008), or involve in a hierarchical manner of delegation, lower areas in the supraspinal nervous system, such as the cerebellum and other subcortical areas (van der Linden et al, 2007), and/or, processes lower down in the spinal cord (Kimura et al, 2006;van der Linden et al, 2007). Related this top-down control, the supraspinal adjustment of long-latency (45-100 ms) reflexes can also draw upon the cerebello-cerebral internal models of limb dynamics (Kurtzer et al, 2008).…”
Section: Top-down Feedforward Motor Adjustmentsmentioning
confidence: 99%